Dwujęzyczność u progu edukacji szkolnej – interdyscyplinarny projekt badawczy - Otwinowska, Agnieszka; Banasik, Natalia; Białecka-Pikul, Marta; Kiebzak-Mandera, Dorota; Kuś, Katarzyna; Miękisz, Aneta; Szewczyk, Jakub; Cywińska, Maria; Kacprzak, Agnieszka; Karwala, Magda; i in. (Neofilolog, 2012)
The paper describes a Polish research project which aims at creating a cognitive and linguistic profile of the Polish-English bilingual child at the school entrance age. With the increase in the number of bilingual children due to economic migrations, researchers, educators and practitioners are often faced with diagnostic dilemmas which arise from similarities in bilingual language acquisition in natural settings and Specific Language Impairment (SLI). The study, which aims at disentangling the effects of bilingualism from those of SLI, is a part of European cooperation programme COST Action IS0408/Bi-SLI. The aim of the Polish team is to create and test a set of tools which can be used for developing norms of typical bilingual development for Polish-English children entering school education.